Cross-cultural translation of the INSPIRIT-R for Brazil and its applicability among epilepsy patients - I S Veronez; M A H Bicalho; L S Claudino; R Walz; K Lin (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe the cross-cultural adaptation of the INSPIRIT-R instrument for evaluation of religious and spiritual experiences into a Brazilian Portuguese version and its applicability among epileptic patients. METHOD: After the translation and back-translation phases, a multidisciplinary committee compared the back-translation with the original text in order to evaluate its content, comprehensibility, conceptual equivalence, cultural and contextual adjustment for Brazilian population. Lastly, the final version was tested on 50 long-term followed-up outpatients with a confirmed diagnosis of epilepsy in Florianópolis, SC, Brazil. RESULTS: The patients' mean age was 33.7 years (18-55) and 26 (52%) were women. They had attended school for a mean of 8.0 years (3-17) years. Most of them (80%) were Catholics and 82% had a confirmed diagnosis of temporal lobe epilepsy. In the final Portuguese version, questions 3, 7C and 7E required slight modifications, along with the layout of question 7. CONCLUSION: The Brazilian Portuguese version of the INSPIRIT-R instrument was easily understood by most of the patients, after minimal modifications.